Nematodes of medical importance in the Philippines, 1907-1977 an annotated bibliography - Rosal, Rosvida R.; Dimalanta, Clarisa G. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1978)
This bibliography brings together under one cover the scattered literature of 25 parasites belonging to phylum NEMATODA of medical importance in the Philippines. It aims to facilitate the literature search and to minimize duplication of research efforts. Following a classified arrangement, the bibliography includes all types of Filipiniana materials, published and unpublished dealing with all aspects of the subject, which were produced from 1907 to 1977. The compilation is limited to parasites affecting man. However, animal parasites which either attack man or the study of which may elucidate certain aspects of human infection are also included. Author and Subject Indexes are provided to facilitate access to the literature.
Includes indexes
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Nematoda -- Bibliography. -- Philippines